The Effect of Leadership on Employee Performance Through Employee Motivation in Primary and Private Dental Clinics in Jakarta - Fitrani Rospita; Andreas Wahyu Gunawan (International Journal Labs, 2023)
In the midst of today's new normal era, the world economy has become very competitive. Many companies are competing to create innovations and make modifications to produce the best service to be provided, especially in the health sector. Health services in the new normal era like today need adaptation in providing services to the community, especially at dental clinics. This study aims to test and analyze